Financial Ratios Governance and Business Risk as Determinants of Corporate Efficiency in Emerging Markets - Henny Setyo Lestari; Maria Carmelia Widiastuti; Rahmadina Ardelia; M. Hussin Abdullah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Efficiency is a critical indicator of a company's performance, reflecting its ability to utilize resources effectively. Previous studies on efficiency have often presented inconsistent findings regarding the influence of financial ratios, corporate governance, and business risk. This study aims to analyze the effect of financial ratios (leverage, liquidity, profitability), good corporate governance, and business risk on the efficiency of manufacturing companies in Indonesia listed on the Indonesia Stock Exchange from 2017 to 2023. The study uses a sample of 67 manufacturing companies selected through purposive sampling, yielding 469 observations over seven years. Panel data regression analysis was employed using EViews 9 software to test the hypotheses. The results indicate that leverage and business risk positively influence company efficiency, while liquidity, profitability, and governance do not show a significant effect. These findings suggest that financial decision-making and risk management play a pivotal role in enhancing efficiency. The study highlights the importance of managing leverage and mitigating business risks to optimize efficiency. Investors should consider these factors when evaluating potential investments. Future research should incorporate additional variables to provide a more comprehensive understanding of efficiency determinants.